A história na diagonal do agora : um conceito contraeducativo para a brecha entre a catástrofe e o novo - reflexões a partir de Arendt e Gur-Ze’ev - Picoli, Bruno Antonio (2019)
This thesis starts from the ask on what educational concept of History can open and keep opened the Now-Time as the opportunity of reflexed action for those that are the new in the world and can offer the novelty to the world. In this sense it searches to authors that have reflected on action and its place in the History and in the Education, as Benjamin, Nietzsche, Adorno, Agamben, Biesta, Gur-Ze’ev and Arendt. In all of them is common the denounce of the old and its preservation strategies, as well as, on the necessity to make of the Now-Time as the action time. In this sense, it stablished the distinction between the present and the Now-Time, the first understood as the simple now, and, the second as a diagonal force in the point of encounter between the past and the future, the point in that the action is possible. It affirms that the present is not taking as the Now-Time because the dominant concept of History joined to the idea of redemption by the progress and it is tied in the causal logic. This situation favours the advancement of catastrophe and of the Exception-rule State that prevents the assumption of responsibility of action for the love of the world. It proposes a concept of History opened to the contingency of each Now-Time from the replacement of the event took as a testimony of the human being profundity as a “Being-able-to-action”. How this concepts faces the catastrophe in defense of the creation of an Exception-efective State opened to the uncertain of action outcomes, this concept of History is a counter-educational concept, that is, it is an ethical and aesthetical attitude in the world that does not adhere to any Utopia, it does not offer a salvation or redemption and it is opened to the uncertain of the novelty. Thus, this thesis is organized in four sections that aim to think the Now-Time as the exclusive time of the opportunity of the action and the inauguration; a new concept to the History that overcomes the conception of History as Progress; The Education as counter-education, and in the end, the articulation among this three dimensions by the proposition of a counter-educational concept of History defiant of the Historical Thinking in the Now-Time Diagonal. The thesis is that the creation of the Exception-efective State, the opening of the Now-Time as the gap between the not-more and the still-not, needs the elaboration of a counter-educational concept of History, that is, of the History opened to the novelty that is possible in every birth to the world by the potential natality in each human being through the action in the time, the illuminating power of the event. It is a concept counter-educational of History because it does not offer a way or a redemption, it does not normalize individuals, it does not model identities and it does not kidnap of the Now-Time the possibilities of the novelty.